NID1 variant associated with occipital cephaloceles in a family expressing a spectrum of phenotypes. Issue 5 (17th February 2019) - McNiven, Vanda; Ito, Yoko A.; Hartley, Taila; Kernohan, Kristin; Miller, Elka; ,; Armour, Christine M.
Abstract : Autosomal dominant Dandy‐Walker malformation and occipital cephalocele (ADDWOC) is a rare, congenital, and incompletely penetrant malformation that is considered to be part of the Dandy‐Walker spectrum of disorders. Affected individuals often present with an occipital cephalocele with a bony skull defect, but typically have normal neurological development. Here, we report on a three‐generation family in which individuals have variable phenotypes that are consistent with the ADDWOC spectrum: arachnoid cysts in the proband and his maternal grandfather, an occipital cephalocele in the proband and his brother, and a small bony defect in the proband's mother. Whole exome sequencing identified a rare heterozygous variant in NID1 (NM_002508.2:c.1162C>T, (p.Gln388Ter)) in the proband, his brother, and his mother. Sanger sequencing confirmed the presence of this variant in the maternal grandfather. The identical c.1162C>T variant was previously identified in variably affected members of a three‐generation family with ADDWOC. This case report provides further evidence that variants in NID1 may be clinically relevant for the development of a phenotype that is consistent with ADDWOC, and extends the phenotype of NID1 ‐associated ADDWOC to include arachnoid cysts. Given that the Dandy‐Walker malformation itself is not a pre‐requisite to this spectrum of phenotypes, we also suggest a novel term for the NID1 ‐associated disorder in order to give emphasis to this phenotypic variability: "Autosomal Dominant Posterior Fossa Anomalies with Occipital Cephaloceles."